Qualidade de vida relacionada à saúde em mulheres no puerpério imediato : uma análise a partir de diferentes tipos de parto - Ribeiro, Samila Gomes (2016)
The quality of life related to health in the postpartum is an important quality indicator of maternal care influenced by sociodemographic, clinical and obstetric factors. This study aimed to analyze the quality of life related to health of women immediately postpartum. It is a cross-sectional, correlational study, performed in a public hospital in the state of Piaui. The sample consisted of 272 women immediately postpartum interviewed from February to June 2015. The instruments used were: a form with sociodemographic, clinical and obstetrical data; the scale for evaluating quality of life Short Form Health Survey (SF-36); The Mother and the index Generated Index (MGI) Brazilian version. Data were compiled and analyzed using the Statistical Package for Social Sciences (SPSS) version 22.0. As for sociodemographic data, the sample was mostly of young mothers, with a mean age of 25.11 years; living with partner 209 (76.8%); They had an average of 10 years of study; 202 (74.3%) did not develop gainful occupation; family income of 125 (69.1%) were between 1 and 3 minimum wages and self-reported race was primarily brown in 201 (73.9%). About obstetric data, 162 (59.6%) were secundiparous / multiparous, 171 (62.8%) had complications during pregnancy and 131 (48.2%) initiated prenatal care after 12 weeks. In assessing the quality of life related to health from the SF-36, the total score averaged 69.94. The areas affected quality of life according to The Mother Generated Index were: Relationship with family; Relationship with her husband; Work; Feelings with the child; More responsibility; Housework; Social life; Sleep; Health; Happiness; Body; Breast-feeding; Feeding. The average primary score was 6.95. By correlating the type of delivery and the professional who attended, the average scores of the Short Form Health Survey (SF-36) showed that the domain limited by physical (41.37), pain (67.53), vitality (62 75), social issues (74.78), limitations due to emotional problems (58.05) and mental health (75.86) had higher averages for vaginal delivery performed by nurses, with statistical significance in the areas: pain (p < 0.05); Vitality (p <0.05) and mental health (p = 0.05). As to age, there was a significant association in the fields functional capacity and general condition, with better scores for age up to 29 years. Regarding schooling, there was significance in the field of "functional capacity" with better scores to 9-11 years of study. The analysis of obstetric complications, showed statistical significance in the field general health p <0.05. There was statistically significant at the crossroads social aspects with the opening of the partograph to 4cm and functional capacity with continued partograph with p <0.05. Therefore, the results pointed to a quality of life related to relatively good health, as well as evidence that vaginal delivery performed by the nurse promotes better scores in quality of life related to health of mothers. It concludes that the achievement of a better quality of life is multifactorial, but the sum of different behaviors can be instrumental in promoting the health of women during pregnancy and childbirth.